2007
DOI: 10.1021/ja075953c
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of 4‘-ThioDNA in the Presence of 4‘-Thio-dTTP and 4‘-Thio-dCTP, and 4‘-ThioDNA-Directed Transcription in Vitro and in Mammalian Cells

Abstract: Herein we describe the synthesis of 4‘-thio-dTTP (1) and 4‘-thio-dCTP (2) and their susceptibility for PCR amplification. Double stranded 4‘-thioDNAs were amplified sufficiently by KOD dash DNA polymerase under appropriate conditions. Through this PCR study, it was shown that not only DNA-directed 4‘-thioDNA synthesis but also 4‘-thioDNA-directed 4‘-thioDNA synthesis occurred in the presence of 1 and/or 2. We then tested the ability of the resulting 4‘-thioDNAs to act as templates for transcription. In this ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 11 publications
1
31
0
Order By: Relevance
“…Using this DNA polymerase, we prepared a modified DNA library involving C5-modified thymidine and successfully screened modified DNA aptamers bound to sialyllactose, R-isomer of thalidomide derivative, and so on by SELEX (23–25). Recently, Inoue et al (69) reported that double-stranded 4′-thioDNAs were directly amplified by PCR using KOD Dash and triphosphates of 4′-thio-nucleoside. Thus, KOD Dash DNA polymerase could accept a broad range of nucleotide modifications and might be best suited for enzymatic preparation of functional modified DNA.…”
Section: Resultsmentioning
confidence: 99%
“…Using this DNA polymerase, we prepared a modified DNA library involving C5-modified thymidine and successfully screened modified DNA aptamers bound to sialyllactose, R-isomer of thalidomide derivative, and so on by SELEX (23–25). Recently, Inoue et al (69) reported that double-stranded 4′-thioDNAs were directly amplified by PCR using KOD Dash and triphosphates of 4′-thio-nucleoside. Thus, KOD Dash DNA polymerase could accept a broad range of nucleotide modifications and might be best suited for enzymatic preparation of functional modified DNA.…”
Section: Resultsmentioning
confidence: 99%
“…2′-Deoxy-4′-thiocytidine 5′-triphosphate (dSCTP) was prepared according to our previous reports. [13] Oligonucleotides were purchased from FASMAC (Kanagawa, Japan). Rhodamine-labeled anti-GFP siRNA (21-mer, 5′-gcugacccugaaguucauctt-3′, 5′-gaugaacuucagggucagctt-3′) was obtained from Invitrogen Life Technologies (Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…These polymerases could accept NTP analogs of 2′-thio (–SH) [17], 2′-amino (–NH 2 ) [19], 2′-azido (–N 3 ) [29], 2′-hydroxymethyl (–CH 2 OH) [33], and 4′-thio (–S–) [39] in addition to 2′-F and 2′-OMe as substrates. Furthermore, NTP analogs with base modification (e.g., C5-modified uridines and cytidines) and with phosphate-modified nucleosides (e.g., 5′-( α -thio)triphosphates and 5′-( α -borano)triphosphates) [21, 30], which are available for modified RNA polymerization, have also been reported.…”
Section: Enzymatic Modified Rna/dna Polymerizationmentioning
confidence: 99%